2016
DOI: 10.2116/analsci.32.1217
|View full text |Cite
|
Sign up to set email alerts
|

Fluidic Culture and Analysis of Pulmonary Artery Smooth Muscle Cells for the Study of Pulmonary Hypertension

Abstract: There is an urgent need to develop novel in-vitro models to mimic the disease conditions in pulmonary hypertension (PH). We developed a microfluidic cell culture device for PH studies that withstood high shear stress. Techniques were also developed for cell recovery from the microchannel and mRNA isolation from the collected cells. Using this device, we found that shear stress caused a 7.5-fold increase in the transcription levels of a PH-related molecule, Cyclin D1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…We have also reported the effects of various culture conditions of vascular endothelial cells, vascular smooth muscle cells, and lymphatic endothelial cells in microchannels. 1,2,[20][21][22] We confirmed that the number of immortalized human microvascular endothelial cells (HMEC-1) was increased day by day in a microchannel with a depth smaller than 100 μm, 22 whereas there was no such increase in the numbers of human dermal microvascular endothelial cells-neonatal (HMVEC-dBINeo) and human dermal lymphatic microvascular endothelial cells-neonatal (HMVEC-dLyNeo). Moreover, although these primary cells proliferated in a conventional polystyrene Petri dish culture, no proliferation was observed in our 65-μm-deep microchannel.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…We have also reported the effects of various culture conditions of vascular endothelial cells, vascular smooth muscle cells, and lymphatic endothelial cells in microchannels. 1,2,[20][21][22] We confirmed that the number of immortalized human microvascular endothelial cells (HMEC-1) was increased day by day in a microchannel with a depth smaller than 100 μm, 22 whereas there was no such increase in the numbers of human dermal microvascular endothelial cells-neonatal (HMVEC-dBINeo) and human dermal lymphatic microvascular endothelial cells-neonatal (HMVEC-dLyNeo). Moreover, although these primary cells proliferated in a conventional polystyrene Petri dish culture, no proliferation was observed in our 65-μm-deep microchannel.…”
Section: Introductionsupporting
confidence: 56%
“…Microchannels were fabricated by a molding process as described previously. 2,24 In brief, the degassed PDMS mixture was poured onto a master to a thickness of 4 mm, which has channel structure of 0.065 × 0.3 × 20, 0.25 × 1 × 10, or 0.5 × 1 × 10 mm (H × W × L), and then baked at 65 C for 1 h. The PDMS replica was peeled off from the master and adhered to a glass slide (26 × 76 mm), and then baked further at 100 C for 1 h. Through-holes were made at both ends of the microchannel with a 1.0-mm biopsy punch. Both bonding surfaces of the PDMS sheet and a cover slip were exposed to oxygen plasma at 100 W for 35 s.…”
Section: Fabrication Of the Microdevicementioning
confidence: 99%
See 3 more Smart Citations